THE ROLE OF DIGITAL FINANCIAL LITERACY IN PROMOTING FINANCIAL INCLUSION FOR RURAL WOMEN AGRIPRENEURS IN NIGERIA - SADIQ MS; SINGH IP; AHMAD MM; ADAMU MY; SANI BS (Innovare Journal of Agricultural Sciences, 2025)
Digital financial literacy (DFL) is increasingly recognized as a critical factor in promoting financial inclusion, particularly for marginalized groups such as rural women agripreneurs in developing nations like Nigeria. This study explores the relationship between DFL and financial inclusion among rural female agricultural entrepreneurs, examining how digital skills impact access to financial services and economic empowerment. Through an extensive review of empirical literature, this paper addresses the unique challenges faced by these women, the role of DFL in overcoming these challenges, and the broader economic and social benefits of increased financial inclusion. Results highlight the importance of targeted educational initiatives, digital infrastructure development, and supportive policy frameworks to foster sustainable growth. This paper concludes with recommendations for stakeholders, including government agencies, non-governmental organizations, and financial institutions, to prioritize DFL as a foundational tool for fostering inclusive economic development in rural Nigeria.